Evaluation of uranium migration during the maturation of hydrocarbon source rocks - Junxian Wang; Ziying Li; Feng He; Fengtian Bai; Linfei Qiu; Jian Guo; Chuang Zhang (Scientific Reports)
Abstract The source of uranium is an important research topic related to the exploration of sandstone-type uranium deposits, and potential uranium sources in deep basins are often overlooked. Black organic-rich shale is a common uranium-bearing rock in deep sedimentary basins. However, relatively few studies have investigated the migration of uranium during hydrocarbon generation in and release from uranium-rich shale. In this study, the uranium-rich shale in the Chang 7 member of the Yanchang Formation of the Upper Triassic in the Ordos Basin was selected to investigate the migration of uranium and other trace elements during the thermal maturation of uranium-rich shale via a semiopen pyrolysis simulation system. The gas and liquid products as well as the solid residue were thoroughly analysed by means of multiple instruments. The results showed that uranium significantly migrated before hydrocarbon generation (Ro < 0.61%), with a leaching rate between 12.1% and 18.8%. The leaching rate of uranium during the hydrocarbon generation stage (0.63% < Ro < 1.35%) was relatively low, ranging from 0 to 7.2%. Cu, Pb, Zn, Mo, and other trace elements also migrated considerably during the early stage of thermal evolution, with leaching rates ranging from 2.9 ~ 11.6%. The yield of low-molecular-weight organic acids (LOAs) was the highest in the early stage of thermal maturity, and the LOA yield exhibited a good correlation with the leaching rates of Cu, Pb, Zn, Co, Mo, etc. The generation of LOAs from source rocks was conducive to the leaching and migration of trace elements. Moreover, according to a statistical analysis of published geochemical data, the total organic carbon (TOC) content, uranium content, and U/TOC ratio in shale decreased significantly with increasing burial depth, indicating that uranium migrated significantly upon kerogen hydrocarbon generation during thermal evolution. Therefore, uranium-rich shale is an important deep uranium source in sedimentary basins.